17β-estradiol biosensors based on different bioreceptors and their applications - Wang, Xinyi; Kong, Fanli; Liu, Yaoyao; Lv, Shiya; Zhang, Kui; Sun, Shutong; Liu, Juntao; Wang, Mixia; Cai, Xinxia; Jin, Hongyan; Yan, Shi; Luo, Jinping (Frontiers in Bioengineering and Biotechnology, 2024)
17β-Estradiol (E2) is a critical sex steroid hormone, which has significant effects on the endocrine systems of both humans and animals. E2 is also believed to play neurotrophic and neuroprotective roles in the brain. Biosensors present a powerful tool to detect E2 because of their small, efficient, and flexible design. Furthermore, Biosensors can quickly and accurately obtain detection results with only a small sampling amount, which greatly meets the detection of the environment, food safety, medicine safety, and human body. This review focuses on previous studies of biosensors for detecting E2 and divides them into non-biometric sensors, enzyme biosensors, antibody biosensors, and aptamer biosensors according to different bioreceptors. The advantages, disadvantages, and design points of various bioreceptors for E2 detection are analyzed and summarized. Additionally, applications of different bioreceptors of E2 detection are presented and highlight the field of environmental monitoring, food and medicine safety, and disease detection in recent years. Finally, the development of E2 detection by biosensor is prospected.